IDENTIFIKASI PUSAT PERTUMBUHAN DAN DAERAH HINTERLAND KOTA PALEMBANG - Imelda Imelda (Jurnal Ekonomi Pembangunan, 2013)
Many reason had been delivered for split policy implementation on a region. Started from economic growth does not appear everywhere and all at once; it appear in points or development poles with variable intensities. The development gap between Palembang Seberang Ulu and Palembang Seberang Hilir is still an unsolved problem. Therefore, need a way out in resolving this problem, that is establish new growth centers in the Palembang city. Base on the focus point, this research purposed to identify the growth center and hinterland on Palembang City at South Sumatera. The data obtain from Central Board of Statistics by using Scalogram analysis to determine the services center based on number and type of units of facilities that exist in any area. The conclusion is the sub-district as the center of economy growth interacting each other with the surrounding sub-district as hinterland. Keywords: Growth Center, Hinterland, Scalogram analysis.